2016
DOI: 10.3402/tellusa.v68.29029
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Hurricane Sandy’s (2012) structure and intensity evolution from full-field and anomaly-field analyses

Abstract: A B S T R A C T An anomaly-based field analysis approach and a set of simple beta-advection models (BAMs) have been used to examine the structure evolution and unusual left turn of Hurricane Sandy (2012) before it made the landfall and caused severe damage along the eastern US coast. Results show that the anomaly-based analysis approach can clearly reveal Sandy's structure evolution, including its interaction with other synoptic-scale systems as well as the intensification and extratropical transition (ET) pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Contributions from both tropical and baroclinic energy sources caused Sandy to reintensify as it approached the coastline (Galarneau et al 2013;Shin and Zhang 2017). The TC followed an atypical track northwestward toward the Northeast United States, rather than out to sea, fostered by interaction with an upstream trough (Barnes et al 2013;Qian et al 2016) of the type identified by Fujiwhara (1931), the practical predictability of which depended on the modeling system (Bassill 2014;Magnusson et al 2014;Torn et al 2015). Sandy tested existing infrastructure for hazard communication (NOAA 2013;Blake et al 2013) and posed challenges related to risk perception (Meyer et al 2014) due to its atypical track and forecast structure (Munsell and Zhang 2014) near landfall.…”
Section: Introductionmentioning
confidence: 99%
“…Contributions from both tropical and baroclinic energy sources caused Sandy to reintensify as it approached the coastline (Galarneau et al 2013;Shin and Zhang 2017). The TC followed an atypical track northwestward toward the Northeast United States, rather than out to sea, fostered by interaction with an upstream trough (Barnes et al 2013;Qian et al 2016) of the type identified by Fujiwhara (1931), the practical predictability of which depended on the modeling system (Bassill 2014;Magnusson et al 2014;Torn et al 2015). Sandy tested existing infrastructure for hazard communication (NOAA 2013;Blake et al 2013) and posed challenges related to risk perception (Meyer et al 2014) due to its atypical track and forecast structure (Munsell and Zhang 2014) near landfall.…”
Section: Introductionmentioning
confidence: 99%
“…New material forms (new states of matter) have emerged at the center of tropical cyclones, such as strong downward and upward air flows as well as an unusually warm core [50]. The central warm core of hurricane Sandy (2012) reached 8˚C -10˚C higher than environmental temperature [51]. The center of the black hole is even less calm, where polar plasma jets appear in the two directions of shear stress.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the "Greenland block", a high-pressure area near Greenland, turned the hurricane towards the northwest coast of the United States [21]. This left turn was unusual [22] and the wind intensified due to a warm seclusion phase [23]. Its effects, such as moderate flooding and sand deposition [24] or soil contamination [25], were noticeable on the coast.…”
Section: Introductionmentioning
confidence: 99%